A case of gynandromorphism in amblyomma mixtum (acari, ixodidae) - Rivera-Páez, Fredy A. [UNESP]; Labruna, Marcelo B.; Martins, Thiago F.; Rodrigues-Sampieri, Bruno [UNESP]; Camargo-Mathias, María I. (SAGE Publications, 2017)
Gynandromorphism is a condition in which an organism simultaneously exhibits male and female morphological characteristics. In Colombia, the taxon Amblyomma cajennense is represented by the species Amblyomma patinoi and Amblyomma mixtum. In September of 2014, in the Colombian Orinoco region, adult ticks were collected and determined from natural infections in bovines and equines. A gynandromorph was described from a natural infestation on a bovine, and morphologically classified as A. mixtum. This is the first literature report of a gynandromorph of A. mixtum, and the first description of a gynandromorph for a tick species in Colombia.
Un caso de ginandromorfismo en amblyomma mixtum (acari, ixodidae)
Keywords: Biology; Neotropic; Ticks